2020
DOI: 10.36227/techrxiv.12145371.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Temporal Forecasting Driven Approach Using Facebook’s Prophet Method for Anomaly Detection in Sewer Air Temperature Sensor System

Abstract: Smart sensor systems play a decisive role in the condition assessment of concrete sewer pipes going through microbial corrosion. Few Australian water utilities adopt a predictive analytic model for estimating the corrosion. They require sensor inputs like sewer air temperature data for corrosion prediction. A sensor system was developed to monitor the daily variation of sewer air temperature inside the harsh sewer environmental conditions. However, a diagnostic tool to evaluate the streaming sensor data is vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Their algorithm, Prophet [39], is based on an additive model where nonlinear trends are fit with seasonality and holidays or other recurrent events. It was applied in numerous studies and achieved state-of-theart (SOTA) performance [40,44]. Recently, NeuralProphet [39,41], a neural network-based extension of Prophet, reached SOTA results for several time series prediction tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Their algorithm, Prophet [39], is based on an additive model where nonlinear trends are fit with seasonality and holidays or other recurrent events. It was applied in numerous studies and achieved state-of-theart (SOTA) performance [40,44]. Recently, NeuralProphet [39,41], a neural network-based extension of Prophet, reached SOTA results for several time series prediction tasks.…”
Section: Related Workmentioning
confidence: 99%
“…The temporal forecasting performance of different models such as Facebook's Prophet method, TBATS model, ARIMA model, ETS model, and the Bagged model were evaluated for forecasting sewer air temperature sensor data. The study outcomes indicated that the performance of Facebook's Prophet method was better in terms of accuracy than other forecasting models for forecasting a week period and a daily period [19]. In this paper, we use the surface temperature sensor data to evaluate the forecasting performances of the seasonal ARIMA model combined with Hyndman and Khandakar algorithm, Facebook Prophet method, ETS model, and Bagged model.…”
Section: Brief Review On Related Workmentioning
confidence: 99%
“…Corrosion is a significant cause of structural degradation in those pipelines. Water utilities assess corrosion conditions using a variety of sensing technologies [1]- [7] in order to avert catastrophic pipe failures. To extend the useful service life of the pipeline and reduce costs associated with pipe replacement, severely corroded pipes are replaced, while moderately corroded pipes are applied with protective linings [8].…”
Section: Introductionmentioning
confidence: 99%